2009
DOI: 10.1016/j.jacc.2009.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Growth After Palliation of Congenital Heart Disease With Duct-Dependent Pulmonary Circulation

Abstract: Percutaneous AD stenting is as effective as MBTS in promoting a global PA growth in CHD-DPC. In addition, it ensures an even distribution of the pulmonary blood flow, thereby promoting a more balanced pulmonary vascular development than MBTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 31 publications
5
41
0
2
Order By: Relevance
“…Early results had reported ductal constriction at sites of exposed ductal tissue after stopping prostaglandin infusion after stent placement [11,12]. More recently, neointimal proliferation within the lumen of the stent has been a common finding [13][14][15][16][17], as was seen in this case. The risks of stent stenosis in a patient with ductal-dependent pulmonary blood flow are significant, and can result in severe cyanosis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Early results had reported ductal constriction at sites of exposed ductal tissue after stopping prostaglandin infusion after stent placement [11,12]. More recently, neointimal proliferation within the lumen of the stent has been a common finding [13][14][15][16][17], as was seen in this case. The risks of stent stenosis in a patient with ductal-dependent pulmonary blood flow are significant, and can result in severe cyanosis.…”
Section: Discussionsupporting
confidence: 52%
“…Improved results have been attributed to advances in technique, catheter delivery systems, and stent technology [13][14][15][16][17]. In our patient, patency of the right AD was maintained by stent implantation as an alternative to the surgical creation of an aortopulmonary artery shunt.…”
Section: Discussionmentioning
confidence: 82%
“…The load generated from the blood flow has little to no effect on the stent structure. The highest percentage was 10 cases take a number of years to occur. It involves a lot cyclic loading due to the arterial wall contraction as a result of heartbeat.…”
Section: B Failure Analysismentioning
confidence: 99%
“…PDA stenting has shown the effective treatment as it performed in modified Blalock-Taussig (mBT) in promoting global pulmonary artery growth as well as control the distribution of blood flow to pulmonary artery [10]. Nevertheless, keeping the ductal patency via wire mesh called stent until the time of definitive repair was remained challenging for long term survival [13] even though the advance technique on coronary intervention for adult has been implementing [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Santoro and colleagues 4 have demonstrated that stenting the patent ductus arteriosus (PDA) is as effective as the mBT shunt in promoting a global pulmonary artery growth and, in addition, ensures an even distribution of pulmonary blood flow. However, keeping the ductus arteriosus reliably patent until the time of definitive repair, generally at 6 to 12 months of age for conduit surgery or first-stage cavopulmonary anastomosis, has remained a challenge until recently.…”
Section: Introductionmentioning
confidence: 99%